On the mechanics of New-Keynesian models - Peter Rupert; Roman Šustek (Queen Mary University of London, School of Economics and Finance, 2016)
We scrutinize the monetary transmission mechanism in New-Keynesian models, focusing on the role of capital, the key ingredient in the transition from the basic framework to DSGE models. The widely held view that monetary policy affects output and inflation in these models through a real interest rate channel is shown to be misguided. A decline in output and inflation is consistent with a decline, increase, or no change in the real interest rate. The expected path of Taylor rule shocks and the New-Keynesian Phillips Curve are key for inflation and output; the real rate largely reflects consumption smoothing.
Keywords: E30; E40; E50; 330; New-Keynesian models; Monetary transmission mechanism; Real interest rate channel; Capital